Optimization of Bacterial Concentrate Media for Lactobacillus Sakei - AP, Nikiforova; SN, Khazagaeva; IS, Khamagaeva (KnE Life Sciences, 2022)
Two strains of lactic acid bacteria were selected for the study (Lactobacillus sakei Lsk-45andLactobacillus sakeiDSM 20017). Bacterial media, based on rice and rice flour, were tested as an alternative to media based on whey. A comparison of the different types of media showed that there was better growth of the selected strains on themedium based on rice flour.Statistical analyses, including factorial experiments and response surface analyses, were used to optimizethe composition of the bacterial medium for Lactobacillus sakei propagation. Bacteriological peptone and rice flour were found to be good growth factors for Lactobacillus sakei.For Lactobacillus sakei Lsk-45,better growth was obtained with the use of 7.75-10 g/L of peptone and 57.5-75 g/L of rice flour. For Lactobacillus sakei DSM 20017, better growth was obtained with the use of 7-10 g/L of peptone and 40-75 g/L of rice flour. Keywords: starters, media, Lactobacillus sakei, fermentation,fish products, bacterial strains, lactic acid bacteria